Dampak Capital Intensity, Ukuran Perusahaan, dan Likuiditas Pada Agresivitas Pajak Perusahaan Property dan Real Estate - Ryke Devianti; Nur Rohma Wahyu Fadhilla; Antoni Antoni (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This research is a quantitative research which aims to find out how the influence of capital intensity, size of firm, and liquidity on tax aggressiveness in various property and real estate listed on Indonesia Stock Exchange for the period 2020-2023. This study uses secondary data obtained through accessing the site www.idx.co.id. Determination of the sample was done by using purposive sampling over a period of 4 years of consecutive observations with a total sample of 40 samples from 10 property dan real estate companies listed on the IDX during 2020-2023. This research data using SPSS version 21 with descriptive statistical test, classical assumption test, multiple linear regression analysis, hypothesis test. The research result concluded as follows:Capital intensity (CIR) had a positive effect on tax aggressiveness, Firm size (SIZE) had a positive effect on tax aggressiveness, Liquidity (Current Ratio) had a positive effect on tax aggressiveness, Capital intensity (CIR), firm size (SIZE), liquidity (Current Ratio) had a positive effect on tax aggressiveness.